Roles of mutual help of local community networks in community health activities: Improvement for the quality of life of older people in Thailand - Khanitta Nuntaboot; Peerapong Boonsawasdgulchai; Nisachon Bubpa (Elsevier, 2019)
Objectives: This study aimed to describe work and activities of community networks focusing on the improvement of the quality of life (QOL) of older people in Thailand. The understanding of the work can help enhancing the community development and strengthening of local communities and their networks. Methods: Qualitative methods including in-depth interview, observation, and focus group discussion were employed to the study. 64 participants participated to the study and were recruited from 4 key actors within the community. Content analysis was used to analyze the obtained data. This study was conducted in 6 local administrative organizations (LAOs) which selected from the outstanding areas of the project. Each LAO represents one sub-district of the regions of Thailand namely; (1) the upper north, (2) the lower north, (3)the upper eastern, (4) the lower eastern, (5) the central and (6) the south. Results: The findings of this study were categorized into three main themes: (1) Social capital including people in the community, social groups, and organizations, (2) Mutual help/collaboration activities composed of six sets of activities related to social capitals working on the improvement of QOL of older people, and (3) Impacts of the mutual help/collaboration activities on older people and local communities who help to improve of QOL of older people. Conclusion: The findings are important features for the community development. These themes should be recommended for community nurses, health related groups and organizations for the improvement of QOL of older people in the community. Keywords: Aged, Community-based participatory research, Community health services, Community networks, Quality of life, Social support